Typology of Strengthening Foundations as Successor to Old Foundations Post Regime Law on Foundations - Mohammad Isrok; Radhityas Kharisma Nuryasinta (Indonesia Law Reform Journal, 2023)
After the Law on Foundations was formed, every Foundation that existed before the enactment of the Law was obliged to adjust its Articles of Association with the provisions of the Law on Foundations. If not, there will be legal consequences for foundations that have not made adjustments, or in other words, the foundation will be legally weak and will also have an impact on the assets/wealth of the foundation. The purpose of this study is to find out the legal implications for new foundations that do not comply with the Foundation Law, as well as find out the typology of strengthening foundations to adjust the condition of their assets by the Foundation Law. With the sociological juridical method, it can be concluded that for foundations that do not adjust their statutes by the Law on foundations, especially related to assets, the foundation will have difficulty managing the ownership of its assets, especially for immovable objects. Then there are two typologies of strengthening to adjust the conditions of the AR Foundation by the Foundation Law, namely from the legality side of law and audit reports. Legal legality emphasizes that achieving accountability and transparency can be carried out through non-litigation efforts which include controlling assets, increasing the capacity of Foundation organs, strengthening supervision, and mediation as well as litigation efforts in the form of court suits. While the typology of strengthening in terms of financial reports, foundations need to have routine reporting standards to report their activities and funding to the Foundation Trustees by financial accounting standards. Keywords: Foundation; Strengthening; Typology.   Abstrak Pasca Undang – Undang tentang Yayasan terbentuk, setiap Yayasan yang lahir/ ada sebelum UU Yayasan wajib untuk menyesuaikan Anggaran Dasarnya dengan ketentuan UU Yayasan. Jika tidak maka akan ada implikasi hukum terhadap Yayasan yang belum melakukan penyesuaian, atau dengan kata lain Yayasan tersebut lemah secara hukum yang turut berdampak (salah satunya) terhadap asset/kekayaan Yayasan. Penyesuaian yang diwajibkan semata-mata bertujuan untuk memberikan penguatan pada sebuah Yayasan yang masih eksis hingga saat ini. Sedangkan penguatan itu sendiri memiliki karakter tertentu yang pada umumnya akan terakumulasi dan muncul sebagai bentuk kesan maupun citra yang diberikan siapa saja terhadap eksistensi Yayasan. Beranjak dari latar belakang yuridis demikian maka penelitian ini menjadikan Yayasan “AR” sebagai objek penelitian, karena berdasarkan observasi peneliti menemukan adanya problem status asset/ kekayaan Yayasan yang disebabkan oleh kurang optimalnya pengelolaan aset yang harus mengacu kepada UU Yayasan. Problem yang demikian menempatkan posisi Yayasan “AR” lemah secara hukum terhadap kepemilikan asetnya, sehingga melalui penelitian ini diharapkan dapat memberikan gambaran objektif mengenai faktor penyebab problem tersebut, dan memberikan solusi mengenai langkah apa saja yang diperlukan untuk memperkuat Yayasan “AR”. Terlebih bahwa Penyesuaian asset/ kekayaan memiliki keterkaitan dengan terbentuknya sebuah klasifikasi penguatan atau yang sering digunakan dengan istilah tipologi penguatan. Guna menjawab permasalahan tersebut, peneliti mengangkat dua buah permasalahan, pertama apa implikasi hukum terhadap Yayasan baru yang tidak menyesuaikan diri dengan UU Yayasan, khususnya terkait asset Lembaga, dan kedua bagaimana tipologi penguatan untuk menyesuaikan kondisi Yayasan baru saat ini dengan ketentuan UU Yayasan. Kata kunci: Penguatan; Tipologi; Yayasan.